Targeting mitochondrial dysfunction in lung diseases: emphasis on mitophagy - Angara, Sureshbabu; Bhandari, Vineet (Frontiers in Physiology, 2013)
During mild stressful conditions, cells activate a multitude of mechanisms in an attempt to repair or re-establish homeostasis. One such mechanism is autophagic degradation of mitochondria or mitophagy to dispose damaged mitochondria. However, if stress persists beyond recovery then dysfunctional mitochondria can ignite cell death. This review article summarizes recent studies highlighting the molecular pathways that facilitate mitochondria to alter its morphological dynamics, coordinate stress responses, initiate mitophagy and activate cell death in relevance to pulmonary pathologies. Thorough understanding of how these signaling mechanisms get disrupted may aid in designing new mitochondria-based therapies to combat lung diseases.